188Re-HEDP therapy in the therapy of painful bone metastases - Liepe, Knut (World Journal of Nuclear Medicine, 2018)
For bone-targeted radionuclide therapy (BTRT), different commercial radiopharmaceuticals are available such as strontium-89, 186Rhenium-hydroxyethylidene diphosphonate (186Re-HEDP), Samarium-153-ethylenediamine tetramethylene phosphonic acid, and radium-223. Unfortunately, the commercial available radiopharmaceuticals are very expensive (from 1,200 to 36,000€ per patient in Europe). The 188W/188Re generator is an ideal source for the long-term (4–6 months) continuous availability of 188Re suitable for the preparation of radiopharmaceuticals for different radionuclide therapies. Labeling at HEDP, it can use cost-effective for BTRT, if enough patients are available for therapy. And so, 188Re-HEDP is the ideal candidate in developing countries which high population to replace the other agents. Two German groups documented a response rate of 80% without any severe side effects and similar bone marrow toxicity compared to the other compounds for 188Re-HEDP. Using 188Re-HEDP in repeated treatments, a prolonged overall survival of repeated to single application was observed (from 4.5 months for single to 15.7 months using ≥≥3 applications).
Keywords: Bone metastases; bone-targeted radionuclide therapy; breast cancer; pain; prostate cancer